Gangguan Komunikasi Publik dan Penurunan Brand Engagement di Perusahaan Toys"R"Us - Diah Ayu Candraningrum (Jurnal Komunikasi Global, 2017)
The world is shocked to hear news of Toys"R"Us toy retail company from the United States filed for bankruptcy to the US government last September 2017. It is inconceivable that the world's largest toy retail company in the world has to close its 1800 store outlets in 38 countries. Using a descriptive qualitative method, the authors investigated the cause of bankruptcy of Toys"R"Us that has stood for 69 years. Through media research and an interview with an online toy player in Indonesia, it is known that the cause of bankruptcy of Lego, Barbie, and Fisher-Prince Product Company is too late to respond to the current digitalized world. Toys"R"Us did not respond quickly to the world's increasingly massive development, especially through the use of new technologies and media. The function and role of Public Relations are not optimized to support the international business communication undertaken. In this case, the role of international Public Relations is needed to improve a positive corporate image so as to attract as many customers or investors as possible. One of them by optimizing the role of Community Relations to improve brand engagement that is part of the brand resonance between companies and their customers around the world. If this potential can be managed properly, it can drive sales growth of Toys"R"Us.